2014
DOI: 10.1097/md.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction and Thrombolytic Therapy in Patients With Acute Ischemic Stroke

Abstract: Renal dysfunction is a prevalent comorbidity in acute ischemic stroke patients requiring thrombolytic therapy. However, the effect of renal dysfunction on the clinical outcome of this population remains controversial.This study aimed to evaluate the safety and effectiveness of thrombolytic therapy in acute stroke patients with renal dysfunction using a meta-analysis.We systematically searched PubMed and EMBASE for studies that evaluated the relationship between renal dysfunction and intravenous tissue plasmino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…It is inevitable to encounter this group of patients requiring rt‐PA for emergent management. Thus, pros and cons of rt‐PA should be carefully weighed by the first‐line clinicians . However, it remains undetermined whether or not rt‐PA will pose a threat for stroke patients with prior CKD.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is inevitable to encounter this group of patients requiring rt‐PA for emergent management. Thus, pros and cons of rt‐PA should be carefully weighed by the first‐line clinicians . However, it remains undetermined whether or not rt‐PA will pose a threat for stroke patients with prior CKD.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, pros and cons of rt-PA should be carefully weighed by the first-line clinicians. 25,26 However, it remains undetermined whether or not rt-PA will pose a threat for stroke patients with prior CKD. 27 The degree of stiffness in the artery structure, namely the tunica intima, varies in the stroke patient groups mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a meta-analysis done by Hao evaluating 7796 stroke patients reported that renal dysfunction did not increase the risk of a poor outcome in patients who received thrombolysis [19]. Nevertheless, in Hao's study, the definition for renal insufficiency was considered as GFR < 60 in 7167 (91.9%) and GFR < 90 in 196 (2.5%) and proteinuria in 432 (5.5%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that patients with renal dysfunction die from indirect causes rather than stroke. Besides, morbidity and mortality can frequently be attributed to other causes such as cardiac disease and susceptibility to infection [19]. …”
Section: Discussionmentioning
confidence: 99%
“…A recently conducted meta-analysis including 14 studies (n = 53,553 patients) has not revealed any significant difference in the odds of poor outcome or ICH between patients with and without renal dysfunction; while the risk of mortality after thrombolytic therapy was significantly higher in patients with renal dysfunction [21] . However, the majority of patients of these studies were from the Western populations and >50% of the data from the metaanalysis were from a US multicenter cohort study with 44,410 participants.…”
Section: Introductionmentioning
confidence: 99%